The world's urban forests : history, composition, design, function and management - McBride, Joe (Springer, 2017)
The purpose of this book is to examine urban forests in cities around the world. It will ask questions about the history, composition, structure, and management of trees in urban areas. Data for this book was collected in 33 cities across broad geographical areas known as biomes. Constraints and opportunities imposed on urban forest composition, design, and management by the ecological characteristics of these biomes will be examined. The book will also address the cultural and historical factors that influenced the characteristics of urban forests around the world.
Keywords: Urban forestry.; Trees in cities.; elektronické knihy; electronic books